2022
DOI: 10.3389/fneur.2022.831832
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Prefrontal and Temporoparietal Repetitive Transcranial Magnetic Stimulation (rTMS) for Treatment of Tinnitus With and Without Comorbid Depression: A Case Series and Systematic Review

Abstract: BackgroundTinnitus distress is related to both the loudness and intrusiveness of the tinnitus percept. Treatment approaches targeting both attentional/limbic and auditory systems may better alleviate tinnitus distress than approaches targeting the auditory system alone.Materials and MethodsTen subjects with chronic tinnitus received sequential rTMS treatment involving: 1) excitatory stimulation administered to the left dorsolateral prefrontal cortex (DLPFC) or inhibitory stimulation administered to the right D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…However, Formanek et al [41] observed "no significant effect of bilateral low-frequency rTMS of the primary auditory cortex and high-frequency stimulation of the left dorsolateral prefrontal cortex" in a group of 20 tinnitus patients. More recently, Noh et al [42], Poeppl et al [43], and Marder et al [44] all reported that dual site rTMS demonstrated efficacy for tinnitus. Noh et al [42] and Marder et al [44] concluded that dual site stimulation was superior to single site rTMS for tinnitus.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, Formanek et al [41] observed "no significant effect of bilateral low-frequency rTMS of the primary auditory cortex and high-frequency stimulation of the left dorsolateral prefrontal cortex" in a group of 20 tinnitus patients. More recently, Noh et al [42], Poeppl et al [43], and Marder et al [44] all reported that dual site rTMS demonstrated efficacy for tinnitus. Noh et al [42] and Marder et al [44] concluded that dual site stimulation was superior to single site rTMS for tinnitus.…”
mentioning
confidence: 99%
“…More recently, Noh et al [42], Poeppl et al [43], and Marder et al [44] all reported that dual site rTMS demonstrated efficacy for tinnitus. Noh et al [42] and Marder et al [44] concluded that dual site stimulation was superior to single site rTMS for tinnitus.…”
mentioning
confidence: 99%
See 1 more Smart Citation